2008
DOI: 10.1111/j.1365-313x.2008.03488.x
|View full text |Cite
|
Sign up to set email alerts
|

A versatile strategy to define the phosphorylation preferences of plant protein kinases and screen for putative substrates

Abstract: SummaryMost signaling networks are regulated by reversible protein phosphorylation. The specificity of this regulation depends in part on the capacity of protein kinases to recognize and efficiently phosphorylate particular sequence motifs in their substrates. Sequenced plant genomes potentially encode over than 1000 protein kinases, representing 4% of the proteins, twice the proportion found in humans. This plethora of plant kinases requires the development of high-throughput strategies to identify their subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 60 publications
5
115
1
2
Order By: Relevance
“…First, OST1, a SnRK2 protein kinase closely linked to ABA receptors, was able to phosphorylate PIP2;1 peptides in vitro. In good agreement with its predicted site specificity (Vlad et al, 2008;Sirichandra et al, 2010), OST1 showed a large preference for loop B Ser-121, whereas two major C-terminal phosphorylation sites (Ser-280 and Ser-283) were not recognized. Second, coexpression of PIP2;1 with OST1 in oocytes enhanced PIP2;1 water transport activity and mutant analysis showed that Stomatal aperture was monitored in Col-0 (black circles), pip2;1-2 (red squares), or pip2;1-2 plants expressing S121A (S121A-1, dark-blue squares; S121A-2, light-blue squares) or S121D (S121D-1, dark-green squares; S121D-2, light-green squares) as described in Figure 1A, except that stomatal opening (t = 0 to 180 min) was induced in the light and in a solution depleted in CO 2 .…”
Section: Aquaporin Phosphorylation and Aba-dependent Signalingsupporting
confidence: 60%
See 1 more Smart Citation
“…First, OST1, a SnRK2 protein kinase closely linked to ABA receptors, was able to phosphorylate PIP2;1 peptides in vitro. In good agreement with its predicted site specificity (Vlad et al, 2008;Sirichandra et al, 2010), OST1 showed a large preference for loop B Ser-121, whereas two major C-terminal phosphorylation sites (Ser-280 and Ser-283) were not recognized. Second, coexpression of PIP2;1 with OST1 in oocytes enhanced PIP2;1 water transport activity and mutant analysis showed that Stomatal aperture was monitored in Col-0 (black circles), pip2;1-2 (red squares), or pip2;1-2 plants expressing S121A (S121A-1, dark-blue squares; S121A-2, light-blue squares) or S121D (S121D-1, dark-green squares; S121D-2, light-green squares) as described in Figure 1A, except that stomatal opening (t = 0 to 180 min) was induced in the light and in a solution depleted in CO 2 .…”
Section: Aquaporin Phosphorylation and Aba-dependent Signalingsupporting
confidence: 60%
“…OST1 kinase activity was assayed essentially as described (Vlad et al, 2008) using the following synthetic peptides (Proteogenix) purified to >80% by HPLC and with the indicated sequences: rbohF, MALDRTRSSAQRKKK; loopB, MALARKVSLPRAKKK; loopB_S121A, MALARKVALPRAKKK; Cter, MASKSLGSFRSAANVKKK; Cter_pS280, MASKSLGpSFRSAANVKKK; and C-ter_S280AS283A, MASKSLGAFRAAANVKKK. In another series of experiments, longer peptides, containing 29 PIP2;1 residues and covering the entire loop B were used.…”
Section: In Vitro Phosphorylationmentioning
confidence: 99%
“…The amino acids surrounding T460 do not constitute a motif identified so far as a preferred sequence for a certain class of kinases nor is it conserved in other proteins known to be phosphorylated (NĂŒ hse et al, 2004;Vlad et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, we still know little about the kinases in plants that are responsible for phosphorylation of the large number of experimentally identified phosphorylation sites. Targets for recombinant expressed plant kinases have been experimentally screened for via either exposure to a substrate peptide mixture and subsequent mass spectrometric analysis of peptide phosphorylation (46) or protein or peptide arrays (47,48). In Arabidopsis, a number of kinase-substrate relationships have been identified through genetic interactions based on crosses of different mutants (see various examples in Ref.…”
mentioning
confidence: 99%